Parallels, interactions and illuminations : traversing Chinese and Western theories of the signs - Ding, Ersu (Toronto studies in semiotics and communication., 2010)
In this groundbreaking work, Ersu Ding studies two traditions of semiotic realism, represented by Plato and Husserl in the West and by Mo Zi and Ouyang Jian in China. They share two fundamental assumptions with regard to meaning: that there exist ultimate qualities of things and states of affairs in the extrasemiotic world and that the meanings of words or other types of sign are derivatives of these essentials. A pioneering work that remains extraordinarily accessible, Parallels, Interactions, and Illuminations explores a wide range of issues, including inter-subjective negotiation of meaning, the relationship between metaphor and culture, and the production and dissemination of myths."--Pub. desc.